2016
DOI: 10.1016/j.psychres.2016.05.044
|View full text |Cite
|
Sign up to set email alerts
|

CRY1 and CRY2 genetic variants in seasonality: A longitudinal and cross-sectional study

Abstract: Cryptochromes are key components of the circadian clocks that generate and maintain seasonal variations. The aim of our study was to analyze the associations of CRY1 and CRY2 genetic variants with the problematicity of seasonal variations, and whether the problematicity of seasonal variations changed during the follow-up of 11 years. Altogether 21 CRY1 and 16 CRY2 single-nucleotide polymorphisms (SNPs) were genotyped and analyzed in 5910 individuals from a Finnish nationwide population-based sample who had fil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 55 publications
1
8
0
Order By: Relevance
“…3) between medaka kept under winter-and summer-like conditions. Candidate gene studies for SAD also reported SNPs in circadian clock genes, including PER2, PER3, BMAL1, CLOCK, NPAS2, and CRY2 (30)(31)(32)(33)(34). We demonstrated a significant decrease in the amplitude of circadian clock gene rhythms in medaka kept under winter-like conditions compared to those in summer-like conditions (Figs.…”
Section: Discussionsupporting
confidence: 56%
“…3) between medaka kept under winter-and summer-like conditions. Candidate gene studies for SAD also reported SNPs in circadian clock genes, including PER2, PER3, BMAL1, CLOCK, NPAS2, and CRY2 (30)(31)(32)(33)(34). We demonstrated a significant decrease in the amplitude of circadian clock gene rhythms in medaka kept under winter-like conditions compared to those in summer-like conditions (Figs.…”
Section: Discussionsupporting
confidence: 56%
“…Several genetic studies have highlighted the relationship between CRY variants and different types of diseases. For example, CRY1 variants have been associated with depression and mood disorders (48)(49)(50), elevated blood pressure and hypertension (49), and insulin resistance (51,52). This clinical heterogeneity implies a variety of different functions for CRY1, potentially caused by different functional domains of the protein.…”
Section: Discussionmentioning
confidence: 99%
“…Kraus et al ( 27 ) determined that although the age at which mortality started increasing did not differ across small and large breeds, once senescence begins, big dog breeds do age more rapidly than small ones. However, Salvin et al ( 17 ) found little evidence for an increased rate of behavioral aging in large, short-lived dogs utilizing a cross-sectional survey, perhaps due to the shorter window of senescence onset and mortality in large breed dogs.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, mixed breed dogs are often assumed to have a phenotypic advantage over pure breeds, resulting in greater longevity, improved health and lower susceptibility to diseases due to higher genetic variation ( 26 , 29 , 35 37 ). However, Salvin et al ( 17 ) found no evidence for differences between pure breed and cross breed dogs in behavioral aging, and health status is dependent almost exclusively on age with no detectable effect of breed ( 34 ). But specific types of morbidities have been found to be breed specific, such as mast cell tumor, lymphoma, granulomatous colitis, and idiopathic epilepsy ( 33 , 38 ).…”
Section: Introductionmentioning
confidence: 99%